Sublingual misoprostol to reduce blood loss at caesarean delivery - Agarwal, Shonali N.; Thakkar, Nidhi D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Caesarean section is the most common obstetrical procedure performed worldwide. Sometimes oxytocin alone is not sufficient to prevent postpartum haemorrhage and additional uterotonics may be required. We attempted an additional uterotonic misoprostol by sublingual route to evaluate the role of it to reduce blood loss at caesarean delivery. Methods: This prospective clinical study was done on patients of S. S. G. Hospital, Baroda; 138 patients who underwent lower segment caesarean section (elective or emergency). The primary outcome was less intra/peri operative blood loss, need for additional uterotonic agents and perioperative haemoglobin (Hb) fall. The secondary outcomes studied were incidence of shivering, pyrexia, nausea, vomiting, operating time, blood transfusion, endomyometritis and hospitalization period. Average blood loss after normal vaginal delivery is 500 ml and after caesarean delivery is around 1000 ml. Results: Mean postoperative Hb was high with misoprostol group and perioperative Hb fall was less. Perioperative Hb fall of 1 g or more was lesser in this group. Conclusions: Sublingual misoprostol reduces intraoperative blood loss, perioperative blood loss and the need for additional uterotonic agents and blood transfusions at caesarean delivery.